PENGARUH PEMBERIAN PAKAN ALAMI Moina sp. DENGAN DOSIS YANG BERBEDA DALAM Feeding Regime TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN LARVA IKAN BAUNG (Hemibagrus nemurus) - Anggi Trisna Dewi; Suminto Suminto; Ristiawan Agung Nugroho (Departemen Akuakultur FPIK UNDIP, 2019)
Baung (Hemibagrus nemurus) is one of the endogeneous freshwater fish that has economic value. Baung still rarely cultivated and only relies on catches, so its need to be cultivated. Live feed must be given the appropriate amount because the fish will grow not optimally if the feed is a few or too much. Moina sp. is one of the live feeds that can be given to baung larvae. The nutritions content of Moina sp. were 37.38% protein, 13.29% fat, 0.00% crude fiber, 11.00% ash, and 99.60% moisture content. Size of Moina sp. that suitable for larvae ranges is 500 – 1,000 μm.The aim of this study was to evaluate the effect of live feed Moina sp. with different doses in feeding regime on growth and survival of larvae baung and to determine the best dose of Moina sp. on growth and survival larvae baung. The research was carried out at the Technical Implementation Unit of the Fish Larvae Center (UPT BBI) Sawangan, Magelang District in March – May 2018. The individuals of D3 larvae with a length of 0.6 ± 0.1 cm were used in the culture. The research was conducted using experimental method with completely randomized design (CRD) with 4 treatments and 3 replicates. Those treatments were treatment A (5ind / ml), B (10 ind / ml), C (15 ind / ml), and D (20 ind / ml).The results showed that the different dose of live feed Moina sp. significantly affected (P <0.01) on TKP, Pm, SGR, EPP, PER and RGR but not significantly affected (P>0.05) on SR. in. treatment D showed the best value of absolute length, SGR and SR in D3D15 stage were 0.9 ± 0.10, 7.04 ± 0.5, 90 ± 3.3,respectivel. In other addition of D15-D28 had absolute length, SGR, FCR, Feed utilization efficiency, PER, RGR and SR were 0.8 ± 0.10, SGR 3.55 ± 0.17 , 1.31 ± 0.1, 76.76 ± 6.2,1.53 ± 0.1, 5.24 ± 0.5, 85.22 ± 3.5. However,20 ind/ml of Moina sp dosage which be recommend for baung larval rearing in hatchery.